Hard Cases and Hard Data: Assessing Corpus Linguistics as an Empirical Path to Plain Meaning - Mouritsen, Stephen C. (Science and Technology Law Review, 2012)
The Plain Meaning Rule is often assailed on the grounds that it is unprincipled—that it substitutes for careful analysis an interpreter’s ad hoc and impressionistic intuition about the meaning of legal texts. But what if judges and lawyers had the means to test their intuitions about plain meaning systematically? Then initial linguistic impressions about the meaning of a legal text might be viewed as hypotheses to be tested, rather than determinative criteria upon which to base important decisions. There exists very little legal scholarship on corpus linguistics—the study of language function and use through large, electronic linguistic databases called corpora—and the role that corpus methods might play in legal interpretation. This omission becomes more and more striking as scholars and jurists (and even the United States Supreme Court) have found themselves persuaded by corpus-based arguments. This Article argues that the plain or ordinary meaning of a given term in a given context is an empirical matter that may be quantified through corpus-based methods. These methods, when applied to questions of legal ambiguity, present significant advantages over existing empirical approaches to plain meaning and over the prevailing intuition-based interpretive approach of many courts. Because large, sophisticated linguistic corpora are widely available and easy to use, and because corpus methods offer a more principled and systematic alternative to the impressionistic interpretation of legal texts, corpus linguistics may one day revolutionize the process of legal interpretation.